Insulinotropic Actions of the Frog Skin Host‐Defense Peptide Alyteserin‐2a: A Structure–Activity Study. (29th June 2013) - Ojo, Opeolu O.; Abdel‐Wahab, Yasser H. A.; Flatt, Peter R.; Conlon, J. Michael
Abstract : Alyteserin‐2a (ILGKLLSTAAGLLSNL.NH2 ) stimulated the rate of insulin release from BRIN‐BD11 clonalβ cells at a concentration of 30 nm (p < 0.05) with a response of 296 ± 26% of basal release at 3 μm (p < 0.001). The insulinotropic actions of analogs containing substitutions byl ‐lysine, d ‐lysine, orl ‐tryptophan at sites that maintain amphipathicity were evaluated. The [G11K], [S7k], [S7k, G11k], and [G11k, N15K] analogs were the most potent stimulating insulin release at 0.01 nm (p < 0.05). The [S7K], [G11K], [S14K], [N15K], [G11k], and [S7K, G11K] analogs were the most effective producing an approximately twofold greater (p < 0.001) release of insulin at 3 μm compared with alyteserin‐2a. The [T8W] and [A9W] analogs were less active than alyteserin‐2a. No peptide‐stimulated release of lactate dehydrogenase at concentrations up to 3 μm, indicating that the integrity of the plasma membrane had been preserved. Membrane depolarization and an increase in intracellular Ca 2+ concentration are involved in the mechanism of action of the peptides. Administration of [G11k]alyteserin‐2a (75 nmol/kg body weight) to high‐fat‐fed mice with obesity and insulin resistance significantly (p < 0.01) enhanced insulin release and improved glucose tolerance during the 60‐min period following an intraperitoneal glucose load. Abstract : XThe [G11K], [S7k], [S7k, G11k], and [G11k, N15K] analogs of alyteserin‐2a stimulated insulin release from BRIN‐BD11 clonal β‐cells at 0.01 nM. Membrane depolarization and an increase in intracellular Ca 2+ concentration are involved in the mechanism of action of the peptides. [G11k]alyteserin‐2a (75 nmol/kg body weight) significantly (p < 0.01) enhanced insulin release and improved glucose tolerance following an intraperitoneal glucose load in high fat‐fed mice with obesity and insulin‐resistance.